318. Treatment Outcomes of Prosthetic Joint Infections: An Internal Assessment of Adherence to Best Practice Guidelines. (26th November 2018) - Horvat, Courtney; Cook, Margaret; Torres, Katherine; Dilworth, Thomas J; Brummitt, Charles F
Abstract: Background: The impact of prosthetic joint infections (PJI) on patient outcomes and health systems is extensive. Patients with PJI may receive nonpreferred antibiotic therapy due to ease of administration, cost, and drug interaction profile. Our objective was to compare treatment of PJI to internal guideline-recommended therapy and assess treatment outcomes. Methods: To reduce heterogeneity of PJI treatment within a large, integrated health system, our antimicrobial stewardship program and orthopedic surgeons created an internal best-practice guideline for treatment of PJI based on published literature. The guideline is organism and surgery specific (Figure 1). Patients who had total knee arthroplasty (TKA) or total hip arthroplasty (THA) and subsequently developed PJI from July 2016 to June 2017 were identified retrospectively. Recurrent infections were defined as recurrence of primary infections or new infections with other organisms. Rates between patients treated with guideline-concordant and guideline-discordant regimens were compared. Results: Among 36 TKAs complicated by PJI, fewer patients who received guideline-concordant therapy experienced recurrent infection than patients who received guideline-discordant therapy (1 of 16 patients [6.25%] vs. nine of 20 patients [45%], P = 0.0219). Among 25 THAs complicated by PJI, there was a trend toward fewer recurrent infections when patients received guideline-concordant therapy (2 of 12 patients [16.7%] vs. 5 of 11 patients [45.5%], P = 0.1775). Common deviations from the guidelines included daptomycin use for methicillin-susceptible Staphylococcus spp. with implant retention due to ease of administration in outpatient settings and avoidance of rifampin due to tolerability or drug interactions. Conclusion: Deviation from treatment guidelines for PJI following TKA and THA may increase the risk of recurrent infection. Barriers to utilizing guideline-recommended antibiotics in the outpatient setting should be addressed. Institutions should develop internal consensus on PJI treatment with prospective surveillance. Disclosures: All authors: No reported disclosures.